An unusual association: duodenal atresia and situs inversus incompletes-a case report and discussion - Zahra, Fatima Al; Khan, Nasir Aziz; Akhtar, Nadeem (International Journal of Contemporary Pediatrics, 2022)
Coming across a number of duodenal atresia in daily practice any paediatric surgeon may conclude that it’s one of the most technically challenging small gut atresia with variations of pathology that has an incidence of 1 in 4000 or 5000 live births. It has marked association with a number of conditions like downs syndrome (trisomy 21) being on crest, accounting for 20-40% of cases. Other prominent associations include VACTERL (vertebral, anotectal malformation, cardiac, tracheo esophageal, renal, limb) anomalies, concurrent other small gut atresias, preduodenal portal vein. A relatively rare association we have come across recently has been situs transverus co existing with duodenal atresia that prompted us to rummage through literature for similar cases embarking us to publish our own finding as very little has been said so far in this regard.